ASSESSMENT OF QUALITY OF LIFE AND DENTAL STATUS OF PATIENTS WITH CHRONIC RECURRENT LIP CHACK - Yulbarsova N.A; Navruzova F.R; Atazhanova Kh.Zh; Tukhtamurodova M.F (Western European Studies, 2024)
The influence of chronic recurrent lip cracks on the condition of the oral cavity, in particular on the condition of periodontal diseases and the hygienic level, has been established. Clinical criteria for assessing the severity of chronic recurrent fissures of the lips are described and options for the severity of the disease are substantiated with an expert assessment of the reliability and convergent validity of the developed criteria
Keywords: chronic recurrent lip chack; oral mucosa; gingivitis